2x-9/x-5 - x2 + 4x-5/x2 - 25 =2x-9/x-5 - (x+5)(x-1)/(x-5)(x+5) =2x-9/x-5 - x-1/x-5 =2x-9-x-1/x-5 =x-10/x-5
2x-9/x-5 - x2 + 4x-5/x2 - 25 =2x-9/x-5 - (x+5)(x-1)/(x-5)(x+5) =2x-9/x-5 - x-1/x-5 =2x-9-x-1/x-5 =x-10/x-5
1. (12y2 - 39y+15+12y3 )/(2y+5) 4. (w3 - 15w-11)/(w-4)
(w3 - 15w - 11) ÷ (w-4)
use long division and the remainder theorem to evaluate P(c), where P(x)= x^3-6x^2+13x-17 c=2
today at home my sister told me that on long division they write m for the meaning of multipalacation and the meaning of s means subtract and b means bring it down plus d means diviision and...
use long division to find the quotient and the remainder when f(x) = 1x^5+6x^4-4x^3+6x^2+7x+1 is divided by 9x^2-7x+5 what is the quotient? what is the remainder...
(long division)
5x3+x2-3x+7 by x-1
(5x^4+2x^3-9x+12)÷(x^2-3x+4)